Tempo de reação a estímulos visuais e infecção por Toxoplasma gondii : uma possível influência do sistema RH - Younan, Karina de Oliveira (2014)
Introduction: The parasite Toxoplasma gondii infects a high percentage of individuals worldwide and disturbances resulting from this infection contribute to the aggravations of health conditions and may affect the intellectual development of children and adults. It has been suggested that the D antigen (Rh0) a glycoprotein that is the biochemical basis Rh but is absent in the nervous tissue, influence the motor response in the presence of T. gondii infection. Objectives: This study aims to evaluate the motor response and the reaction time for visual stimulus in the presence and in the absence of infection by the parasite T. gondii in individuals with good visual acuity, Rh positive and Rh negative. Methods: 212 volunteers from both sexes underwent visual acuity testing and measurement of average response time to visual stimulus (ART) by using a specific software. The collected blood samples were used to identify the erythrocyte RH phenotypes (positive and negative) and antibodies of IgG class anti-T. gondii (presence or absence). Average response times were compared according to sex, presence (reagents) and absence (non-reagent) infection and erythrocyte Rh phenotypes (positive and negative). The t test for comparison of average and the values of Odds Ratio (OR) and 95% confidence interval were calculated using the GraphPad Instat (version 6.3) software. The p-value equal to or less than 0.05 was considered significant. Results: The differences between the average age of reagents individuals (n = 134) and non-reagent (n = 38) to T. gondii were considered statistically significant (54.1 ± 18.7 vs 34.4 ± 18.9; p = 0.0001). The Rh phenotype positive (n = 189) was present in 89% of individuals, while the Rh-negative (n = 23) in 11%. The ART of reagents individuals for T. gondii was lower in males (0.672 ± 0.303) than in females (0.819 ± 0.270) (p = 0.0036). This same difference was observed between the non-reagent (0.475 ± 0.140 vs 0.791 ± 0.323), respectively (p <0.0001). Infected men (0.658 ± 0.282) had higher ART xi than uninfected men (0.488 ± 0.129) for T. gondii, both Rh positive (p = 0.0004). Women, infected or not, did not differ for ART even when compared by phenotype (positive or negative) Rh. Conclusions: Rh positive men infected with T. gondii have a higher ART than uninfected Rh positive men. Infected women do not differ in ART compared to women uninfected by T. gondii.